Clinical and scintigraphic comparison of silicone and polyvinylpyrrolidone coated silicone perforated plugs. Issue 12 (1st December 1998) - Malet, Th; Challier, B; David, N; Bertrand, A; George, J-L
Abstract : BACKGROUND/AIM: Isolated stenosis of the lacrimal punctum is a frequent cause of epiphora. Treatment relies on surgical opening or dilatation with bi- or monocanalicular prosthesis. Recently, silicone perforated punctum plugs (PPP) were proposed. The drawback with these silicone PPP was that secretions accumulate in the central orifice blocking the spontaneous flow of tears. A modification of the surface of the PPP using polyvinylpyrrolidone (PVP) was thus proposed. The aim was to compare silicone PPP with new PVP surface treated PPP. METHODS: A prospective study was conducted of 20 patients with dilatable stenosis of the lacrimal puncta who developed epiphora. Epiphora, tolerance, implantation of the PPP, and lacrimal drainage were evaluated using scintigraphy of the lacrimal ducts. RESULTS: The raw data and statistical analysis showed evidence of a superior performance of PVP surface treated PPP. CONCLUSION: Long term evaluation of the advantages or risks of PVP plugs and comparison with microsurgical punctoplasty are warranted.